Effect of CaCl2 Sprays in Different Fruit Development Stages on Grape Berry Cracking - Shi, Hao; Zhou, Xiangyu; Qin, Mengling; Wang, Wenlong; He, Xiaoe; Zhou, Wenhua (Frontiers in Plant Science, 2022)
Grape cracking is a common phenomenon that can reach more than 50% in some varieties and can cause enormous economic losses. “Li Xiu” grapes in different developmental stages were treated with calcium chloride (5 g/L), and the cracking rate and related biochemical and genetic indices were measured in the fruit ripening stage. The results showed that calcium treatment during the flowering period could significantly reduce grape cracking. Based on the experimental results, there are several reasons as follows: first, calcium spraying during the flowering period was more favorable to calcium absorption in grapes, and the increased calcium content in the peels helped to improve the mechanical properties of the peels, thus increasing crack resistance; second, calcium treatment reduced the expression levels of genes related to glucose metabolism, which in turn reduced PG and cellulase activities, delaying the degradation of pectin and cellulose and resulting in more structural integrity of the peels; third, calcium treatment increased fruit hardness and reduced fruit ventral pressure by decreasing the expression levels of ABA-related genes and synthesis of endogenous abscisic acid (ABA), soluble sugars (SSs), and total soluble solids (TSSs).